2019
DOI: 10.1177/0886109919866161
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Survivors Who Exchange Sex: Identity, Stigma, and Informal Responses From Support Providers

Abstract: It is well established in the literature that individuals who engage in sex work are more likely to experience sexual trauma/violence, but little research has examined experiences of sexual assault survivors who exchange sex from the survivor’s perspective. Sexual assault survivors and their informal support providers (SPs; e.g., family, friends, romantic partners) were interviewed separately about disclosure, social reactions, and help-seeking following assault. Sixteen survivors mentioned experiences exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(70 reference statements)
2
3
0
Order By: Relevance
“…FEWs might be more likely to seek emotional support within their accessible support systems, such as friends, colleagues, or family members. This finding is consistent with a qualitative study in the United States that examined the experiences of FSWs who survived sexual assault (Shepp et al, 2020). The result revealed that some informal supporters, including family, friends, and intimate partners, expressed their empathy and understanding of the survivors (Shepp et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…FEWs might be more likely to seek emotional support within their accessible support systems, such as friends, colleagues, or family members. This finding is consistent with a qualitative study in the United States that examined the experiences of FSWs who survived sexual assault (Shepp et al, 2020). The result revealed that some informal supporters, including family, friends, and intimate partners, expressed their empathy and understanding of the survivors (Shepp et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with a qualitative study in the United States that examined the experiences of FSWs who survived sexual assault (Shepp et al, 2020). The result revealed that some informal supporters, including family, friends, and intimate partners, expressed their empathy and understanding of the survivors (Shepp et al, 2020). Informal supporters could encourage women to seek services following the experience of violence.…”
Section: Discussionsupporting
confidence: 86%
“…This leads to risky sexual behaviour in women and the life experiences of street women in the city. The study revealed that sexual violence has been increasing the exchange of sex [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is totally possible, but not always the case, for people feel that their body is still theirs after performing sex work. In the article Sexual Assault Survivors Who Exchange Sex, the authors found that '23.5% of sexual assault survivors engaged in sex work following their assault' (Shepp et al 2020). Additionally, they pointed out how, for sex workers, 'engaging in sex work was related to regaining control over both their lives and bodies post-assault,' and that 'child sexual abuse and sexual assault in adolescence or adulthood may also serve as a pathway to engaging in sex work, through running away from abuse at home... and/or making it difficult to set boundaries and develop healthy sexuality later in life (Shepp et al 2020).…”
Section: The Nuances Of Sex Work By Georgia Langermentioning
confidence: 99%
“…The stigma around sex work, LGBTQ+ identities, and sexual assault makes it difficult for victims to receive aid. One study found that 44 percent of street-based sex workers have been sexually assaulted by the police (Shepp et al 2020). According to the Washington Post, the statistic for U.S. rapist felony convictions is about 0.7%.…”
Section: The Nuances Of Sex Work By Georgia Langermentioning
confidence: 99%